GAMBARAN SIKLUS MENSTRUASI PADA DIET KETOGENIK - RIZKY SYAHRIANI; AMELIA EKA DAMAYANTY (JURNAL ILMIAH KOHESI, 2022)
The ketogenic diet is a diet that uses a source of fat as an energy source and reduces carbohydrate consumption. If the carbohydrate or calorie calories are too low, it can hold back leptin levels and interfere with leptin's ability to regulate hormones. The study aims to overview the menstrual cycle on ketogenic diet. Analysis descriptive with cross-sectional approach. The respondents were 118 respondents. Based on the menstrual cycle, most respondents with polymenorrhea were 36 people (30%), olygomenorrhea were 20 people (17%), amenorrhea were 7 people ((6%), and normal cycle were 55 people. Based on the menstrual cycle, most respondents with polymenorrhea were 36 people (30%).